Youth crime, urban spaces and security in Germany since the 19th century = Jugendkriminalität, städtische Räume und Sicherheit in Deutschland seit dem 19. Jahrhundert - Weinhauer, Klaus (2010)
"This article focuses on juvenile delinquency and on its perceptions in the last thirds of the 19th and of the 20th centuries. Three questions are discussed: Were there any debates on (human) security in both time phases and if yes, which problems were discussed; which larger social developments were mirrored in these debates; what were the implications of potential threats posed by juvenile delinquency for life in urban settings? In the last third of the nineteenth century the perception of and fears about youth crime focused on easily discernable proletarian male youth (groups and individuals) who mainly lived in densely populated urban neighborhoods. As (youth) crime was mainly interpreted as a threat towards the state and authorities were convinced that the police could successfully handle all challenges in this field, there were no debates about security at that time. In West Germany during the 1960s and the 1970s, two important changes in juvenile delinquency, in its percepti